Automatic Water Desalination Device using Sugeno Fuzzy Logic (Case Study: Tangkil Coast) - Ilham Firman Ashari; Ahmad Auzan Varian Syahputra (Department of Electrical Engineering, 2022)
Water desalination is the process of making fresh seawater or the process of making fresh water from salt water. This study uses a thermal desalination process because the salt content produced is less than the results from membrane desalination. This fuzzy method also has several variations in its application. The fuzzy Sugeno method used in this study differs from other methods, that is, with this method the results are in the form of constants or linear equations so that they can automate the desalination process. Tangkil Island is used as the object in this case study because it is a center for family tourism but has difficult access to fresh water. This study tested the results of desalination water by using a salinity measuring instrument with the type of salinity-615 as the standard for reading salt levels. The comparison results have an error value of above 50% due to the difference in the reading digits of the salinity-615 tool, which only has a value of 1 digit behind the comma, so that the results compared with the salt level sensor (embedded), which can read 3 digits behind the comma, have a high error percentage. The results of the tests carried out using Matlab with the actual conditions at the temperature, humidity, and water level observed that the desalination process runs automatically. From the results of these tests, there are very large differences in the calculation of the evaporation rate. The temperature and humidity factors can change at any time, which causes very large differences from the calculation results. In line with the increase in temperature and decrease in humidity, the evaporation process will be faster but will experience a slowdown in the evaporation process if the opposite occurs.